ENHANCING EMPLOYABILITY THROUGH ENTREPRENEURSHIP EDUCATION IN INDIA’S COMMERCE AND MANAGEMENT INSTITUTES - Dr. Najmus Sehar (International Educational Journal of Science and Engineering, 2025)
This research paper explores the transformative impact of the National Education Policy (NEP) 2020 on entrepreneurship education in commerce and management institutes in India. The study reveals a substantial increase in institutions offering specialized entrepreneurship courses and a surge in student participation since NEP 2020 implementation. The rise of over 250 active startup incubators and accelerators, supported by governmental initiatives, signifies a vibrant entrepreneurial ecosystem. Data indicates a 35% increase in graduate employability and a remarkable 40% growth in startups founded by young entrepreneurs. The paper emphasizes entrepreneurship education’s role in job creation, innovation, GDP contribution, and supporting Sustainable Development Goals. Challenges in curriculum design, faculty training, resource access, and impact evaluation are discussed. Success stories like RedBus and Zomato underscore entrepreneurship education’s potential. Recommendations include dynamic curriculum design, interdisciplinary approaches, industry integration, mentorship, and soft skills focus. Strategic initiatives like entrepreneurship clubs, on-campus incubators, alumni engagement, and government-industry partnerships are proposed for fostering a robust entrepreneurial culture.